2016
DOI: 10.1186/s12936-016-1432-1
|View full text |Cite
|
Sign up to set email alerts
|

Anti-malarial seroprevalence assessment during an elimination programme in Chabahar District, south-eastern Iran

Abstract: BackgroundIran has achieved a substantial decline in malaria incidence over the past decades. A common feature of malaria-endemic settings is the requirement for more sensitive techniques to describe levels of low transmission. In this study, serological and parasitological methods were used to measure transmission levels of Plasmodium falciparum and Plasmodium vivax during an elimination programme (2012) in Chabahar District, Sistan and Baluchistan Province, south-eastern Iran.MethodsParticipants were randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…It seems that “previous” P. vivax transmission in this study was lower in more remote settlements than in the forest fringe area, indicating lower potential receptivity for the re-introduction of malaria in the settlements in this district. The heterogeneity in malaria exposure within communities due to the difference in location has also been reported in other settings ( Rosas-Aguirre et al., 2013 ; Idris et al., 2017b ; Kale et al, 2019 ; Zakeri et al., 2016 ; Labadie-Bracho et al., 2020 ; Rahim et al., 2022 ). Therefore, further monitoring of seroprevalence and population movement between different settlements is considered highly effective, given the different risks of malaria transmission within the study area.…”
Section: Discussionsupporting
confidence: 61%
“…It seems that “previous” P. vivax transmission in this study was lower in more remote settlements than in the forest fringe area, indicating lower potential receptivity for the re-introduction of malaria in the settlements in this district. The heterogeneity in malaria exposure within communities due to the difference in location has also been reported in other settings ( Rosas-Aguirre et al., 2013 ; Idris et al., 2017b ; Kale et al, 2019 ; Zakeri et al., 2016 ; Labadie-Bracho et al., 2020 ; Rahim et al., 2022 ). Therefore, further monitoring of seroprevalence and population movement between different settlements is considered highly effective, given the different risks of malaria transmission within the study area.…”
Section: Discussionsupporting
confidence: 61%
“…The proportion of seropositive individuals, as well as the magnitude of serological response increased with age, which provides further evidence of the decrease in transmission in this area. A positive age-dependent seroconversion pattern has previously been reported from areas with low Plasmodium transmission intensity [ 32 35 ]. The presence of antibodies to several Plasmodium antigens in children under five years of age, however, can be considered as a marker of relatively recent exposure [ 36 ] and provides evidence of continued low-intensity transmission in the area that needs to be monitored.…”
Section: Discussionmentioning
confidence: 87%
“…In these studies, antibody responses to crude parasite extract were determined using an immunofluorescence antibody test (IFAT). More recently, studies from Aneityum and Iran suggested absence of transmission by assessing antibody responses to individual recombinant antigens (apical membrane antigen 1; AMA-1, and the 19 kDa fragment of merozoite surface protein 1; MSP-1 19 ) (7,8) or schizont extract (7) using an enzyme-linked immunosorbent assay (ELISA). Similar to the historical studies, children showed no antimalarial antibody responses, while some adults did have antimalarial antibodies owing to the persistence of antibodies (and/or memory B cells) once acquired (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%